3D kinematic in freestyle cross-country skiing (XCS) technique during World Cup races and World Championships - Canclini, A.; Canclini, A.; Baroni, G.; Pozzo, R. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The "new" freestyle (FT) in XCS was formally introduced in 1985 in specialized races in addition to the original races in classical technique. In the last threedecades the freestyle has considerably developed due to the new equipment and materials, better ski tracks preparation, increasing in the training methodology and in the enhanced skiers techniques depending in terrain and/or drag forces. In the `90s several studies have been conducted in attempt to describe the most relevant aspects of XCS freestyle, but the kinematic information is generally limited in the velocity range. More recently Kvamme (2005), Smith (2007), Lindinger (2010), Stöggl (2010), Andersson (2010) compared biomechanical characteristics of the main skating techniques identified as V1, V2 and V2A (old names) or gears G2, G3 and G4 as proposed by Nilsson (2004). The purpose of this work was to collect and to analyze the 3D kinematics of the main gears (G2,G3,G4) in freestyle XCS performed by elite skiers engaged in recent World Cup and WChS races